Case Report: Effectiveness Of Brexpiprazole And Esketamine/ketamine Combination: A Novel Therapeutic Strategy In Five Cases Of Treatment-resistant Depression - Lai Fong Chan; Luke Sy-Cherng Woon; Nuur Asyikin Mohd Shukor; Choon Leng Eu; Nurazah Ismail; Song Jie Chin; Nik Ruzyanei Nik Jaafar; Azlin Baharudin (Frontiers Media S.A, 2024)
Indexed by WOS/SCOPUS/ERA